2015
DOI: 10.1016/s0924-9338(15)31077-4
|View full text |Cite
|
Sign up to set email alerts
|

Medical Resident's Burnout: About 149 Cases

Abstract: Background: Burnout is a professional psychological chronic stress-induced syndrome defined by three dimensions: emotional exhaustion, depersonalization and low personal accomplishment. It concerns all professions especially healthcare staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…The prevalence rate of BOS in this study was similar to a study conducted among resident physicians in Greece, in which 14.4% of residents met the criteria for BOS [28]. Moreover, a cross-sectional survey in Tunisia concluded that 17.14% of resident physicians had a high level of BOS [33]. Another study in Syria reported a 19.3% prevalence rate of burnout syndrome among resident physicians [40].…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence rate of BOS in this study was similar to a study conducted among resident physicians in Greece, in which 14.4% of residents met the criteria for BOS [28]. Moreover, a cross-sectional survey in Tunisia concluded that 17.14% of resident physicians had a high level of BOS [33]. Another study in Syria reported a 19.3% prevalence rate of burnout syndrome among resident physicians [40].…”
Section: Discussionsupporting
confidence: 86%
“…Similar to a study conducted among resident physicians in Greece, in which 14.4% of residents met the criteria for burnout [23]. Additionally, a cross sectional survey in Tunisia concluded that 17.14% of resident physicians had a high level of burnout [28].…”
Section: Discussionsupporting
confidence: 62%